Human perforin employs different avenues to damage membranes. - Praper, T; Sonnen, A; Viero, G; Kladnik, A; Froelich, C; Anderluh, G; Dalla Serra, M; Gilbert, R (2011)
Perforin (PFN) is a pore-forming protein produced by cytotoxic lymphocytes that aids in the clearance of tumor or virus-infected cells by a mechanism that involves the formation of transmembrane pores. The properties of PFN pores and the mechanism of their assembly remain unclear. Here, we studied pore characteristics by functional and structural methods to show that perforin forms pores more heterogeneous than anticipated. Planar lipid bilayer experiments indicate that perforin pores exhibit a broad range of conductances, from 0.15 to 21 nanosiemens. In comparison with large pores that possessed low noise and remained stably open, small pores exhibited high noise and were very unstable. Furthermore, the opening step and the pore size were dependent on the lipid composition of the membrane. The heterogeneity in pore sizes was confirmed with cryo-electron microscopy and showed a range of sizes matching that observed in the conductance measurements. Furthermore, two different membrane-bound PFN conformations were observed, interpreted as pre-pore and pore states of the protein. The results collectively indicate that PFN forms heterogeneous pores through a multistep mechanism and provide a new paradigm for understanding the range of different effects of PFN and related membrane attack complex/perforin domain proteins observed in vivo and in vitro.